2013
DOI: 10.1371/journal.pone.0063369
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Countermeasure Discovery against Francisella tularensis Based on a Metabolic Network Reconstruction

Abstract: In the future, we may be faced with the need to provide treatment for an emergent biological threat against which existing vaccines and drugs have limited efficacy or availability. To prepare for this eventuality, our objective was to use a metabolic network-based approach to rapidly identify potential drug targets and prospectively screen and validate novel small-molecule antimicrobials. Our target organism was the fully virulent Francisella tularensis subspecies tularensis Schu S4 strain, a highly infectious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 70 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…Methods for therapeutic target discovery based on metabolic pathway analysis and metabolic network modeling have become very popular in the last ten years. Numerous studies have identified candidate drug targets in various bacterial (27,34,(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102), fungal (102) and protosoan (31,(102)(103)(104)(105) pathogens using a variety of methods to analyze metabolic pathways and networks. One method employs chokepoint analysis to identify metabolic enzymes that are critical to the pathogen, because they uniquely consume and/or produce certain metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for therapeutic target discovery based on metabolic pathway analysis and metabolic network modeling have become very popular in the last ten years. Numerous studies have identified candidate drug targets in various bacterial (27,34,(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102), fungal (102) and protosoan (31,(102)(103)(104)(105) pathogens using a variety of methods to analyze metabolic pathways and networks. One method employs chokepoint analysis to identify metabolic enzymes that are critical to the pathogen, because they uniquely consume and/or produce certain metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…However, their crystallographic asymmetric unit contains dimer and functional tetramers were obtained using two-fold crystallographic symmetry. The H. pylori GmhA is the only homologue, which was observed as homodimer in solution 15 , 16 .…”
Section: Resultsmentioning
confidence: 99%
“…A multidisciplinary approach was applied to F. tularensis to select a group of enzymes as drug targets and ~20,000 small-molecule compounds were screened to list potential inhibitors against these targets (Chaudhury et al, 2013 ). A set of 40 candidate compounds was identified for antimicrobial activity against F. tularensis .…”
Section: Genome-scale Metabolic Models Of Pathogenic Microorganisms Amentioning
confidence: 99%